Predictors of the Severity and Duration of Treatment of Sepsis-Associated Delirium - N. A. Rezepov; Yu. V. Skripkin; O. N. Ulitkina; O. A. Grebenchikov; V. V. Likhvantsev (Общая реаниматология)
Mental illnesses in patients with sepsis occur in 23—32% of cases and are an unfavorable prognostic sign. At present, the causes of these disorders are adequately explained by the theory of neuroinflammation that takes into account the pathogenic influence of the systemic inflammatory reaction and related endothelial dysfunction on the central nervous system function.The purpose of the study was to evaluate the relevance of the severity of the systemic inflammatory response, the intensity of oxidative stress and the severity of patient's general state to prediction of the duration of delirium and therapy outcomes in patients with sepsis-associated delirium.Materials and methods. A pilot, single-center, prospective, cohort study was performed in 187 adult patients diagnosed with sepsis who were treated in the intensive care unit of L. A.Vorokhobov Municipal Clinical Hospital No. 67. The following tests and examinations were performed: Vasoactive-Inotropic Score (VIS), Sepsis-related Organ Failure Assessment score (SOFA), Intensive Care Delirium Screening Checklist (ICDSC); plasma levels of carbonylated peptides, procalcitonin (PCT), and neuromarkers were monitored; and a correlation analysis with the severity of the sepsis, its duration and therapy outcomes was performed.Results. A moderate correlation (R=0.68; P<0.05) between the plasma concentration of carbonylated peptides and the duration of delirium was found. The S100b protein level, a marker of neuronal damage, also closely correlated (R=0.75; P<0.05) with the duration of delirium. In the group of ICDSC, SOFA, and VIS, the latter turned out to be the most significant predictor of the delirium duration (P=0.02). In the group in which SOFA, carbonylated peptides and PCT levels monitored, the organ failure scale was the leading one (P=0.02).Conclusion. The vasoactive-inotropic score (VIS) is a more relevant predictor of the delirium duration than ICDSC and SOFA; the organ failure scale assessment has a greater correlation with the delirium duration than carbonylated peptides and PCT level monitoring; the VIS is the best predictor of the mortality in patients with sepsis.